Uji Sensori Dan Vitamin C Zat Besi Cookies Substitusi Tepung Kacang Merah Dan Tepung Wortel - Anggita Cahyani; Novia Zuriatun Solehah; Laksmi Nur Fajriani (Universitas Muhammadiyah Semarang, 2026)
Adolescent girls are susceptible to anemia due to iron deficiency and an unbalanced diet. Red beans are rich in iron and vegetable protein, while carrots contain vitamin C which helps iron absorption. Utilization of both in the form of cookies is expected to produce nutritious, long-lasting, and preferred functional food. This study aims to analyze the differences in cookie formulations with substitution of red bean flour and carrot flour on iron content, vitamin C, proximate test, and organoleptic acceptance. The method used is a one-factor Completely Randomized Design (CRD) with 5 (five) treatments, namely the addition of carrot flour as much as 35 g., 30 g, 25 g, 20 g, 15 g and the addition of red bean flour as much as 65 g, 70 g, 75 g, 80 g, 85 g. The organoleptic test carried out consisted of 35 semi-trained panelists. Meanwhile, the chemical quality test was carried out 2 (two) times. The results showed that the addition of red bean flour and carrot flour increased the iron content in the product statistically giving a significant effect (p <0.05) which was 0.015. The vitamin C content tends to decrease with increasing proportion of red bean flour, statistically giving a significant effect (p<0.05) of 0.000. The proximate test shows that the addition of red bean flour and carrot flour has a significant effect (p<0.05) on water content (0.001), protein (0.002), carbohydrate (0.000) and fat (0.020) but has no significant effect (p>0.005) on ash content (0.680).